Design Android-Based E-book Application for Sundanese Pupujian Teaching Materials - Ripai, Ipan; Ropiah, Opah; Sukma Nur Alam, Fajar (JTP - Jurnal Teknologi Pendidikan, 2022)
An android-based e-book application for teaching materials is a type of electronic book in softcopy. This study aims to design an android-based e-book application for Pupujian Sundanese teaching materials and determine its feasibility. This research is development research (R&D). The flow in this research are: 1) potential problems: 2) data collection; 3) product design: 4) design validation; 5) design revision; 6) product trial; 7) product revision; 8) trial use; 9) product revision; 10) mass production. Based on design validation, this application is feasible to test because the percentage is 85.00% - 100.00%. This product was tested on students of the Regional Language and Literature Education Study Program, STKIP Muhammadiyah Kuningan. Based on the pretest and posttest results, the average value of the pretest was 56.42, while the posttest obtained an average value of 77.21. It can be concluded that the android-based e-book application for Sundanese Pupujian teaching materials is "appropriate" to be implemented in learning and can be mass-produced.